Cultural value creation through batik tulis as a religious tourism souvenir: A purple economy perspective from Indonesia - Rokhmat Subagiyo; Ahmad Syaichoni; Ahmad Budiman; Binti Nur Asiyah; Ahmad Sodiq; Nana Pangestu (Academic Bright Collaboration, 2026)
This study aims to analyze the value creation of Batik Tulis as a religious tourism souvenir through the perspective of the purple economy in the pilgrimage-based religious tourism area of the Tomb of Sheikh Ibrahim Asmoroqondi, Tuban, East Java, Indonesia. The pilgrimage-based setting matters for this process because devotional experience at the tomb embeds the souvenir with spiritual and identity-based meaning that is central to how its cultural value is formed, rather than the souvenir functioning as an ordinary tourist commodity. This study uses a qualitative approach with a case study design. Data were collected through in-depth interviews with 11 informants, participatory observation, documentation, and literature review, and were analyzed through data condensation, data display, and conclusion drawing. Data management was supported by NVivo, with source and method triangulation and member checking. Within this single religious tourism site, Batik Tulis functions as a marker of pilgrimage experience and local identity. However, recognition of cultural value does not automatically lead to purchase because of price sensitivity, practicality, market access, and limited digital literacy. Economic value emerges when cultural meaning is mediated through storytelling, digital marketing, product diversification, and collaboration among craftspersons, tourism actors, and local government. This study highlights the importance of managing cultural products as part of the broader ecosystem of religious tourism experience, rather than merely as commodities. This study offers a purple economy reading, showing that cultural value in local religious destinations in Indonesia becomes economic value only when mediated by storytelling, visitor experience orchestration, digital market access, and multi-stakeholder collaboration.